Determination of Isoenzyme Variation in Some Medicago sativaEcotypes - AGAR, GULERAY; SENGUL, MERYEM; SENGUL, SULEYMAN; YILDIRIM, NALAN (Asian Journal of Chemistry, 2010)
This study was carried out in order to determine variation of Medicago sativa ecotypes, using Polyacrylamide Slab Gel Electrophoresis (PAGE) on the 5 enzyme systems (PRX, MDH, PPO, SOD, GDH). Differences between ecotypes were analyzed statistically. The highest genetic distance was between Dilburnu, Diableverde and the least was between Dilburnu, Çayirbasi. The results from isoenzyme analysis correlated with some morphological characteristics. This study of Medicago sativa ecotypes suggests that the geographical and ecological distribution of the plants contributes to higher genetic similarity.